Early Identification of Stress-Related Growth (SRG) as a Substitute Approach to Preserving Parents' Mental Health of Children with Neurodevelopmental Disorder - Purwaningsih, Erwin; Umar, Zulkifli; Nurhasanah, Nurhasanah (STMIK Widya Cipta Dharma, 2024)
Approximately 90% of suicide cases are linked to mental illnesses or psychological issues. Data from the World Health Organization (WHO) indicate that up to 450 million individuals worldwide experience stress. Additionally, data from the Centers for Disease Control and Prevention (CDC) reveal that 1 in 6 children globally suffer from neurodevelopmental disorders as of 2023. Having a child with an intellectual disability can significantly impact family functioning. This research explores the use of digitally-based health transformations to develop a system for early stress-level monitoring, integrated with therapeutic media tailored to psychological challenges. The primary objective is to evaluate the effectiveness of LYTERATH's initiative in providing E-THALY media to parents of children with neurodevelopmental disorders. The Methdod of this research is using a quasi-experimental study was conducted using a pretest-posttest control group design. The sample included 66 respondents, divided into two groups, selected through proportionate random sampling. And the result for this research is the Paired T-Test results demonstrated that the intervention group, which used the E-THALY application, showed a significant improvement in early stress detection, with a p-value of 0.036 (< 0.05). Stress levels were significantly different before and after the intervention. In contrast, the control group, which only received mental health literature, showed no significant changes, as indicated by a p-value of 0.277 (> 0.05). Based on these results, it can be concluded that the integration of electronic therapy is highly effective in improving mental health outcomes, and the digitalization of health programs plays a crucial role in managing parental stress levels. It is hoped that these efforts will contribute to reducing the prevalence of mental health-related morbidity and mortality.